Exploring the Cognitive-Affective Components of Body Image Disturbance in Adolescent Girls - Acar, Zeynep (Psychology of Woman Journal, 2025)
Objective: This study aimed to explore the cognitive and affective components of body image disturbance (BID) in adolescent girls. Methods and Materials: A qualitative research design based on a phenomenological approach was employed to investigate the lived experiences of 20 adolescent girls aged 13–18 from various regions in Malaysia. Participants were selected through purposive sampling and took part in in-depth, semi-structured interviews, which were conducted in private settings to ensure confidentiality and comfort. Data collection continued until theoretical saturation was achieved. Interviews were transcribed verbatim and analyzed thematically using NVivo 14 software. The analysis followed Braun and Clarke’s six-step method, incorporating both inductive and deductive coding strategies to identify recurrent cognitive, emotional, and behavioral patterns. Findings: Four overarching themes emerged: (1) Cognitive Evaluations of Body Image, including internalized ideals, social comparison, and self-objectification; (2) Affective Experiences, such as shame, anxiety, and body-related emotional fluctuations; (3) Sociocultural Influences, encompassing family, peer, media, and cultural pressures; and (4) Coping and Regulation Strategies, which ranged from avoidance and compensatory behaviors to cognitive reframing and peer support. Participants described a dynamic and often distressing relationship with their bodies, marked by internalized societal expectations and emotionally charged self-appraisal. Conclusion: This study highlights the interrelated cognitive and affective processes underlying BID in adolescent girls, emphasizing the role of sociocultural context in shaping these experiences. The findings underscore the need for holistic, culturally sensitive interventions that address not only distorted thoughts but also emotional regulation and social influences.